Social Perception of Risk-Taking Willingness as a Function of Expressions of Emotions - Hareli, Shlomo; Elkabetz, Shimon; Hanoch, Yaniv; Hess, Ursula (Frontiers in Psychology, 2021)
Two studies showed that emotion expressions serve as cues to the expresser’s willingness to take risks in general as well as in five risk domains (ethical, financial, health and safety, recreational, and social). Emotion expressions did not have a uniform effect on risk estimates across risk domains. Rather, these effects fit behavioral intentions associated with each emotion. Thus, anger expressions were related to ethical and social risks. Sadness reduced perceived willingness to take financial (Study 1 only), recreational, and social risks. Happiness reduced perceived willingness to take ethical and health/safety risks relative to neutrality. Disgust expressions increased the perceived likelihood of taking a social risk. Finally, neutrality increased perceived willingness to engage in risky behavior in general. Overall, these results suggest that observers use their naïve understanding of the meaning of emotions to infer how likely an expresser is to engage in risky behavior.